Fragmented Justice: How the Wedding Cake Model is Influenced by the 'No Viral, No Justice' Phenomenon - Kadir, Zul Khaidir (MultiTech Publisher, 2024)
One relevant model for understanding how the justice system classifies cases is the wedding cake model. However, the existence of social media has presented new challenges. Ironically, viral cases jump over the traditional hierarchy in this model. This study uses a qualitative research method with a conceptual approach. The results of the study show that the phenomenon of